Joro's youth : the first part of the Mongolian epic of Geser Khan - Rachewiltz, Igor de, 1929-2016; Narangoa, Li (ANU Press, 2017)
Contains a retelling of the first seven episodes (bȯlȯg) of Mongolian saga of Gesar, focusing on the youth Joro before he became the King Gesar. Not a literal or literary translation. The original poetry is translated as a tale and includes a few poems.